Crude Oil Price and Exchange Rate: An Analysis of the Asymmetric Effect and Volatility Using the Non Linear Autoregressive Distributed Lag and General Autoregressive Conditional Heterochedasticity in Mean Models - Saidi, La Ode; Aedy, Hasan; Saranani, Fajar; Rosnawintang, Rosnawintang; Adam, Pasrun; Sani, La Ode Arsad (International Journal of Energy Economics and Policy, 2019)
This study aims to examine the asymmetric effect of crude oil price and volatility on exchange rate. The price of WTI crude oil is a proxy for crude oil, while IDR/USD exchange rate is a proxy for exchange rate. The time series of both WTI crude oil price and IDR/USD exchange rate span the period of January 2006 to December 2017. To test the asymmetric effect, the NARDL-GARCH-M model is used. The results of the analysis show that in the short-term there is an asymmetric effect of crude oil price and volatility on the IDR/USD exchange rate while in the long-term such effect does not exist. Keywords: Crude oil prices, exchange rates, volatility, NARDL model, GARCH-M model JEL Classifications: C120, C320, E310, G150 DOI: https://doi.org/10.32479/ijeep.8362